Flood disaster indicator of water level monitoring system - Wan Haszerila Wan Hassan; Aiman Zakwan Jidin; Siti Asma Che Aziz; Norain Rahim (Institute of Advanced Engineering and Science, 2019)
The early warning systems for flood management have been developed rapidly with the growth of technologies. These system help to alert people early with the used of Short Message Service (SMS) via Global System for Mobile Communications (GSM). This paper presents a simple, portable and low cost of early warning system using Arduino board, which is used to control the whole system and GSM shields to send the data. System has been designed and implemented based on two components which is hardware and software. The model determines the water level using float switch sensors, then it analyzes the collected data and determine the type of danger present. The detected level is translated into an alert message and sent to the user. The GSM network is used to connect the overall system units via SMS.